BERINGOVSKY BASIN COALS METAMORPHISM - G. A. Fandyushkin (Известия высших учебных заведений: Геология и разведка)
Main type of coals metamorphism in Beringovsky basin is stated to be regional. According to the degree of carbonification coals of the basin change from long-flame to fat (the I-III stages of a metamorphism). A degree of a metamorphism of deposited coals increases with stratigraphic depth and with increase of the thicknesses of strata covering them. The most metamorphosed coals are dated to the places of the greatest deileciions, the least metamorphosed - to the consedementation raisings. The area of distribution of the coked coals in the deposit is specified. A degree of a metamorphism of the coals in the Beringovsky basin was studied mainly on the basis of the reflective ability of a vitrinit (RAV)